2016
DOI: 10.1038/srep23318
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of optically directed self-assembly of nanoparticles

Abstract: Self-assembly of nanoparticles leading to the formation of colloidal clusters often serves as the representative analogue for understanding molecular assembly. Unravelling the in situ structure and dynamics of such clusters in liquid suspensions is highly challenging. Presently colloidal clusters are first isolated from their generating environment and then their structures are probed by light scattering methods. In order to measure the in situ structure and dynamics of colloidal clusters, we have generated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In single NPs level, Goswami et al have reported that femtosecond laser enables manipulation and construction of 250 nm PS NPs with a specific 3D geometry. Not only optical trapping potential but also assembly of NPs can be controlled by femtosecond laser polarization 53,54 . Two-photon fluorescence is used for tracking the movement of individual NPs and for analyzing their geometry 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In single NPs level, Goswami et al have reported that femtosecond laser enables manipulation and construction of 250 nm PS NPs with a specific 3D geometry. Not only optical trapping potential but also assembly of NPs can be controlled by femtosecond laser polarization 53,54 . Two-photon fluorescence is used for tracking the movement of individual NPs and for analyzing their geometry 55 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are explained in terms of single transient assembly formation in the optical trap. In the single NP level, Goswami et al have reported that the femtosecond laser enables manipulation and construction of 250 nm PS NPs with a specific 3D geometry. Not only optical trapping potential but also assembly of NPs can be controlled by femtosecond laser polarization. , Two-photon fluorescence is used for tracking the movement of individual NPs and for analyzing their geometry . Even the hierarchical self-assembly was demonstrated and discussed, which will be a useful reference for fabricating the assembly as the bottom-up approach.…”
Section: Discussionmentioning
confidence: 99%
“…The other is the structuring of NPs will be more controllable by laser power and polarization. For example, Goswami et al demonstrated for different configurations of a few 250 nm PS NPs by utilizing femtosecond laser in solution. This interesting trial enables individual arrangement in NP assembly at the solution surface and interface too.…”
Section: Resultsmentioning
confidence: 99%
“…The assembly formation of NPs by femtosecond laser in single NPs level is studied by Goswami et al. They manipulated dye‐doped 250 nm PS NPs and constructed a specific 3D geometry, [78,79] where two‐photon fluorescence is used for tracking the movement of individual NPs and for analyzing their geometry [80] . Even hierarchical self‐assembly was demonstrated and discussed, [81] which will be a useful reference for fabricating the assembly as the bottom‐up approach.…”
Section: Summary and Perspectivementioning
confidence: 99%